FIRE SENSING SYSTEM - Redaksi Tim Jurnal (Sutet, 2017)
The current fire hazard is increasingly common, not only from human error or also gas leakage and the use of electrical equipment that does not detect earlier the possibility of fire and this tool is a fire sensing system. The work system is meant by some of the same ways and the occurrence of fire that exist in a room, and provide it with a buzzer. The purpose of making this tool is for an alarm system that can share a fire and explain how the process works. The result of making this tool, the sensor managed to detect the heat caused by the fire and buzzer issued an alarm sound.